A case of primary cerebral venous thrombosis. Issue 590 (December 1974) - Brookfield, D. S. K.
Abstract : A case of primary cerebral thrombophlebitis is described in a young man, who had a thrombotic diathesis. The patient initially presented with a right phlegmasia alba dolens which was treated with anticoagulants, surgery and thrombolytic therapy. Over 2 years later he developed a further phlegmasia and what was clinically thought to be a meningitis. Despite anti-coagulation he died from a progressive cerebral venous thrombosis.